Effect of Cellulose Loading Ratio on Fiber-Matrix Bonding of LDPE-Based Biocomposite - Yoobsan Ejeta Amensisa; Hundessa Dessalegn Demsash; Muluken Eshetu Tefera (Advances in Materials Science and Engineering)
The properties of biocomposite materials have been highly affected by the amount of cellulose particles and/or fibers added to the matrix during manufacturing. The objective of this study was to determine the effects of the cellulose loading ratio (CLR) on the fiber-matrix interfacial bonding of the biocomposite made of extracted celluloses from coffee husk (CH) and brewer’s spent grain (BSG) fibers with recycled post-consumer low-density polyethylene (r-LDPE) matrix. The test samples were prepared using the solvent casting method with different CLRs of 10wt.%, 15wt.%, and 20wt.% and abbreviated as BC-10%, BC-15%, and BC-20%, respectively. The study was carried out using the Vickers microhardness test (VMH), thermogravimetric analyzer (TGA), scanning electron microscopy (SEM), and water absorption test. The study findings show that the maximum Vickers hardness value (Hv1) of 17.16 kgf/mm2 was obtained in the BC-15% composite sample. TGA showed that BC-10% and BC-15% exhibited good thermal behavior compared to BC-20%. Based on SEM microstructure image analysis, moderate fiber-matrix interfacial bonding was observed. The water absorption test indicated that as the CLR increases, the water absorption rate of the composite samples also increases. In general, an increase in the CLR could influence some principal properties such as hardness, thermal stability, fiber-matrix compatibility, and water absorption rate of cellulose/r-LDPE biocomposites.